Operando monitoring of the functional role of tetrahedral cobalt centers for the oxygen evolution reaction - Yonggui Zhao; Nanchen Dongfang; Chong Huang; Rolf Erni; Jingguo Li; Han Zhao; Long Pan; Marcella Iannuzzi; Greta R. Patzke (Nature Communications)
Abstract The complexity of the intrinsic oxygen evolution reaction (OER) mechanism, particularly the precise relationships between the local coordination geometry of active metal centers and the resulting OER kinetics, remains to be fully understood. Herein, we construct a series of 3 d transition metal-incorporated cobalt hydroxide-based nanobox architectures for the OER which contain tetrahedrally coordinated Co(II) centers. Combination of bulk- and surface-sensitive operando spectroelectrochemical approaches reveals that tetrahedral Co(II) centers undergo a dynamic transformation into highly active Co(IV) intermediates acting as the true OER active species which activate lattice oxygen during the OER. Such a dynamic change in the local coordination geometry of Co centers can be further facilitated by partial Fe incorporation. In comparison, the formation of such active Co(IV) species is found to be hindered in CoOOH and Co-FeOOH, which are predominantly containing [CoIIIO6] and [CoII/FeIIIO6] octahedra, respectively, but no mono-μ-oxo-bridged [CoIIO4] moieties. This study offers a comprehensive view of the dynamic role of local coordination geometry of active metal centers in the OER kinetics.